The returns to schooling in rural China: Evidence from the Cultural Revolution education expansion - Terry Sicular; Juan Yang (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2015)
During the Cultural Revolution China embarked on a remarkable, albeit temporary, expansion of post-primary education in rural areas. This education expansion affected tens of millions of children who reached secondary school age in the late 1960s and 1970s. Exploiting the education expansion and variation across birth cohorts, we estimate the returns to schooling in rural China using household survey data from the mid-1990s. Our estimated returns of 11 to 20 percent are substantially higher than most previous estimates. We calculate the impact of the education expansion on subsequent labor market outcomes of the affected cohorts and find that they enjoyed significantly higher earnings than pre- and post-expansion cohorts.
Keywords: I21; I28; J24; J31; O15; 330; education expansion; secondary education; returns to schooling; rural China; Cultural Revolution